Finite Element Modeling of Thermo-Viscoelastoplastic Behavior of Dievar Alloy under Hot Rotary Swaging - Izák, Josef; Benč, Marek; Opěla, Petr (Tech Science Press, 2025)
The paper deals with the FEM (Finite Element Method) simulation of rotary swaging of Dievar alloy produced by additive manufacturing technology Selective Laser Melting and conventional process. Swaging was performed at a temperature of 900°C. True flow stress-strain curves were determined for 600°C–900°C and used to construct a Hensel-Spittel model for FEM simulation. The process parameters, i.e., stress, temperature, imposed strain, and force, were investigation during the rotary swaging process. Firstly, the stresses induced during rotary swaging and the resistance of the material to deformation were investigated. The amount and distribution of imposed strain in the cross-section can serve as a valuable indicator of the reduction in porosity and the texture evolution of the material. The simulation revealed the force required to swag the Dievar alloy. It also showed the evolution of temperature, which is important for phase transformation during solidification. Furthermore, microstructure evolution was observed before and then after rotary swaging. Dievar alloy is a critical material in the manufacture of dies for high-pressure die casting, forging tools, and other equipment subjected to high temperatures and mechanical loads. Understanding its viscoelastoplastic behavior under rotary swaging conditions is essential to optimize its performance in these demanding industrial applications.

The paper deals with the FEM (Finite Element Method) simulation of rotary swaging of Dievar alloy produced by additive manufacturing technology Selective Laser Melting and conventional process. Swaging was performed at a temperature of 900°C. True flow stress-strain curves were determined for 600°C–900°C and used to construct a Hensel-Spittel model for FEM simulation. The process parameters, i.e., stress, temperature, imposed strain, and force, were investigation during the rotary swaging process. Firstly, the stresses induced during rotary swaging and the resistance of the material to deformation were investigated. The amount and distribution of imposed strain in the cross-section can serve as a valuable indicator of the reduction in porosity and the texture evolution of the material. The simulation revealed the force required to swag the Dievar alloy. It also showed the evolution of temperature, which is important for phase transformation during solidification. Furthermore, microstructure evolution was observed before and then after rotary swaging. Dievar alloy is a critical material in the manufacture of dies for high-pressure die casting, forging tools, and other equipment subjected to high temperatures and mechanical loads. Understanding its viscoelastoplastic behavior under rotary swaging conditions is essential to optimize its performance in these demanding industrial applications.
Finite Element Modeling of Thermo-Viscoelastoplastic Behavior of Dievar Alloy under Hot Rotary Swaging
Keywords: FEM; rotary swaging; SLM; selective laser melting; dievar; ingot casting; hot work tool steel; additive manufacturing; FEM; rotary swaging; SLM; selective laser melting; dievar; ingot casting; hot work tool steel; additive manufacturing